Study on Macroeconomic Factor’s Impact on Initial Public Offerings (IPO) in India: An examination of the impact of macroeconomic factors on initial public offerings (IPOs) in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper looks at Effect of initial public bids on the market share (IPOs) in India between 199394 and 201516 of macro-economic variables such as the interest rate, the bursary index and remittances. Factors like stock price index and transfer of goods are more important the interest rate in comparison to IPOs has a lower impact. The issue of a greater number of IPOs has also been linked to increasing secondary equity exchange operation, increased cash flow and a company declining market interest rate.